2003
DOI: 10.1103/physrevb.68.165308
|View full text |Cite
|
Sign up to set email alerts
|

Interaction corrections to two-dimensional hole transport in thelargerslimit

Abstract: The metallic conductivity of dilute two-dimensional holes in a GaAs HIGFET (Heterojunction Insulated-Gate Field-Effect Transistor) with extremely high mobility and large rs is found to have a linear dependence on temperature, consistent with the theory of interaction corrections in the ballistic regime. Phonon scattering contributions are negligible in the temperature range of our interest, allowing comparison between our measured data and theory without any phonon subtraction. The magnitude of the Fermi liqui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
80
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 32 publications
4
80
2
Order By: Relevance
“…The latter assumption is believed to be justified for Si-based and some (those with a very large spacer) GaAs structures, and the results of Refs. 18,19,20 have been by and large confirmed by most recent experiments 26,27,28,29,30,31,32 on such systems. On the other hand, the random potential in typical GaAs heterostructures is due to remote donors and has a longrange character.…”
Section: Introductionsupporting
confidence: 59%
“…The latter assumption is believed to be justified for Si-based and some (those with a very large spacer) GaAs structures, and the results of Refs. 18,19,20 have been by and large confirmed by most recent experiments 26,27,28,29,30,31,32 on such systems. On the other hand, the random potential in typical GaAs heterostructures is due to remote donors and has a longrange character.…”
Section: Introductionsupporting
confidence: 59%
“…In other words the 2DHG shows 'metallic' behaviour at low T. Such nonmonotonic behaviour has been observed earlier in n-and p-GaAs heterojunctions and QWs [11][12][13]. It is found that T 0 depends approximately linearly on p (see figure 4).…”
supporting
confidence: 74%
“…A.12 corresponds to the third diagram with the equilibrium vertex, which is given by K(q, ω) = 1 πν n τ dp (2π) n γ G A (p, ǫ)G R (p + q, ǫ + ω) 13) and the rest of the diagram is described by the function L(q, ω) = 1 πν n τ dp (2π) n G A (p, ǫ)G R (p + q, ǫ + ω)…”
Section: Discussionmentioning
confidence: 99%